2023
DOI: 10.29303/jima.v2i1.2290
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Pemberian Pupuk Anorganik dan Pupuk Organik Cair (POC) Limbah Air Cucian Beras Terhadap Pertumbuhan dan Hasil Tanaman Sawi (Brassica juncea L.)

Abstract: Penelitian ini bertujuan untuk mengetahui pengaruh pemberian pupuk anorganik dan Pupuk organik cair (POC) limbah air cucian beras terhadap pertumbuhan dan hasil tanaman sawi (Brassica juncea L.). Penelitian dilakukan pada bulan Juni 2022 sampai Agustus 2022, di Jempong Baru, Pegesangan Barat, Kecamatan Mataram. Penelitian disusun menurut rancangan Acak Lengkap faktorial dengan dua faktor, pertama dosis pupuk anorganik urea, SP36, dan KCl dan kedua volume POC. Faktor pertama terdiri atas tiga taraf perlakuan ya… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
1
0
0
Order By: Relevance
“…From the data above it can be concluded that each frequency of liquid organic fertilizer application gives an increase in the number of leaves in each WAT (week after treatment), the highest value for the increase in the number of leaves is obtained at the frequency of application with an interval of 1 week with an average value of 9.63 in 12 MSP, and the lowest mean value is at the frequency of giving 3 weeks once a week with a value of 4.56 at 4 MSP. This is in accordance with the opinion of [13], that the frequency of applying fertilizer with different doses causes the production of different numbers of leaves and the right frequency will accelerate the rate of leaf formation.…”
Section: Number Of Leavessupporting
confidence: 91%
“…From the data above it can be concluded that each frequency of liquid organic fertilizer application gives an increase in the number of leaves in each WAT (week after treatment), the highest value for the increase in the number of leaves is obtained at the frequency of application with an interval of 1 week with an average value of 9.63 in 12 MSP, and the lowest mean value is at the frequency of giving 3 weeks once a week with a value of 4.56 at 4 MSP. This is in accordance with the opinion of [13], that the frequency of applying fertilizer with different doses causes the production of different numbers of leaves and the right frequency will accelerate the rate of leaf formation.…”
Section: Number Of Leavessupporting
confidence: 91%